2002
DOI: 10.1051/0004-6361:20020779
|View full text |Cite
|
Sign up to set email alerts
|

Lithium abundances from the 6104 Å line in cool Pleiades stars

Abstract: Abstract. Lithium abundances determined by spectral synthesis from both the 6708 Å resonance line and the 6104 Å subordinate line are reported for 11 Pleiades late-G and early-K stars observed at the William Herschel Telescope. Firm detections of the weak subordinate line are found for four objects, marginal detections for four, and upper limits for the remaining three stars. Some of these spectra were previously analysed by Russell (1996), where he reported that abundances derived from the 6104 Å line were sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…In a related paper (Ford et al 2002) we found evidence that 6104 gave higher Li abundances than 6708 for some young Pleiades G/K dwarfs, whilst for others there seems to be reasonable agreement. This is very similar to the situation we find here for Pop.…”
Section: Contrast With Pop I Starsmentioning
confidence: 56%
See 1 more Smart Citation
“…In a related paper (Ford et al 2002) we found evidence that 6104 gave higher Li abundances than 6708 for some young Pleiades G/K dwarfs, whilst for others there seems to be reasonable agreement. This is very similar to the situation we find here for Pop.…”
Section: Contrast With Pop I Starsmentioning
confidence: 56%
“…Recent work by Kurucz (1995), Carlsson et al (1994), Stuik et al (1997), Uitenbroek (1998) and Asplund et al (1999) has suggested that this line might be unrepresentative of the actual Li abundance within the stars, due to omissions in our understanding and modelling of stellar atmospheres. Recent works on halo stars (Bonifacio & Molaro 1998, hereafter BM98 -and next subsection) and young cluster stars (Soderblom et al 1993a;Russell 1996;Ford et al 2002) have used the weak (excitation potential = 1.8 eV) Li  subordinate line at 6104 Å in addition to the 6708 Å line (hereafter 6708 and 6104 are taken to mean "the Li  line at 6708 Å" and "the Li  line at 6104 Å" respectively), to attempt to determine Li abundances. This paper builds on those previous studies.…”
Section: +019mentioning
confidence: 99%
“…Stars studied Chemical elements Pilachowski et al (1987) 18 A, F, G Li Burkhart & Coupry (1997) 8 A-Am Li, Al, Si, S, Fe, Ni, Eu Hui- Bon-Hoa & Alecian (1998) 9 A-Am Mg, Ca, Sc, Cr, Fe, Ni 1 2F F e 1 2F C Boesgaard et al (2003) 1 4Fa n dG B e Ford et al (2002) 1 1Ga n dK L i Table 2. Data on the programme stars.…”
Section: Referencementioning
confidence: 99%
“…Careful analysis of the subordinate lithium line at 610.4 nm by Ford, Jeffries & Smalley (2002) indicates that the spread in lithium abundances among Pleiades stars with the same mass may be real.…”
Section: Introductionmentioning
confidence: 99%